Skena “Teras Kolektif”: Dinamika Kolektiva dan Resistensi Musik Mahasiswa - Justito Adiprasetio; Annisa Winda Larasati (Calathu: Jurnal Ilmu Komunikasi, 2020)
Teras Kolektif is a music collective that is active in Jatinangor, carrying the spirit of punk and the culture of Do It Yourself. But unlike other punk scenes, Teras Kolektif does not carry the essentialist burden which is always obedient to the puritanism of music and other identity standards. Teras Kolektif scene arises from the anxiety of students who want a space where a frame of “old-fashioned” morality does not tie them up. This study relies on participatory ethnography as a methodology, with the aim of capturing the dynamics and various behavioral pattern of the Teras Kolektif. Data collection techniques were also strengthened by in depth interviews with 18 subjects consisting of actors as well as those who intersected directly with Teras Kolektif activities. The findings of this study are that the Teras Kolektif is a student public sphere, where not only music is mixed, but also where political discussion and education take place. Teras Kolektif also succeeded in becoming a space for discourse exchange between students on various campuses. There are things that need to be evaluated by Teras Kolektif as a progressive collective: the hyper-masculine character that is at risk of damaging the spirit that they carry, also related to the regeneration of the Teras Kolektif to maintain its existence and consistency going forward.